Miradi Measures Dashboard Demo - Salzer, D (2013)
Live demonstration (view in HD) of a new online measures dashboard sit e (http://miradi.sitkatech.com) that allows users of the Miradi Adapti ve Management software (http://miradi.org) to share the progress they are making towards achieving their desired results